Strontium Ion Removal From Artificial Seawater Using a Combination of Adsorption With Biochar and Precipitation by Blowing CO2 Nanobubble With Neutralization - Guo, Yixuan; Hong Nhung, Nguyen Thi; Dai, Xiang; He, Chunlin; Wang, Youbin; Wei, Yuezhou; Fujita, Toyohisa (Frontiers in Bioengineering and Biotechnology, 2022)
While enjoying the convenience of nuclear energy development, the environmental contamination by radionuclide leakage is of significant concern. Because of its cost-effectiveness and environmental friendliness, biochar has attracted a lot of attention in the field of radioactive water treatment. Herein, a novel teak peel modified biochar (labeled as PMBN3) was prepared and applied to remove strontium from artificial seawater. The characterisation of the prepared PMBN3 showed it contains numerous oxygen-containing functional groups (i.e. carboxyl and hydroxyl groups), laminar morphology, mesoporous structure, large specific surface area. PMBN3 exhibited great advantages in Sr(II) adsorption, such as rapid adsorption kinetics (<1 h for equilibrium) and superior reusability. The adsorption of strontium by biochar is consistent with pseudo-second order and internal diffusion kinetic kinetic models. Among the four types of adsorption isotherms, the Freundlich isotherm showed the best fit with R2 > 0.98. The calculated thermodynamic parameters indicate that strontium adsorption on biochar occurs exothermically and spontaneously. Furthermore, for efficient removal of Sr(II), CO2 nanobubbles were blown into artificial seawater to precipitate the interfering metal ions, and followed by the adsorption of PMBN3 towards residual metal ions with the removal rate of Sr(II) over 99.7%. Finally, mechanistic studies have shown that the strontium adsorption process by PMBN3 is a multiple adsorption mechanism consisting of ion exchange between H+ (from -OH and -COOH) and Sr(II), and weak intermolecular forces between Sr(II) and the PMBN3 adsorbent. This study creatively combines chemisorption and nanobubble precipitation for strontium removal, which provides great reference value and guidance for environmental remediation.